Designing Historical Social Scientific Inquiry: How Parameter Heterogeneity Can Bridge the Methodological Divide between Quantitative and Qualitative Approaches. Issue 2 (20th August 2013) - Wawro, Gregory J.; Katznelson, Ira
<x xml:space="preserve">Abstract</x> Seeking to advance historical studies of political institutions and behavior, we argue for an expansion of the standard methodological toolkit with a set of innovative approaches that privilege parameter heterogeneity to capture nuances missed by more commonly used approaches. We address critiques by prominent historians and historically oriented political scientists who have underscored the shortcomings of mainstream quantitative approaches for studying the past. They are concerned that the statistical models ordinarily employed by political scientists are inadequate for addressing temporality, periodicity, specificity, and context—issues that are central to good historical analysis. The innovations that we advocate are particularly well suited for incorporating these issues in empirical models, which we demonstrate with replications of extant research that focuses on locating structural breaks relating to realignments and split‐party Senate delegations and on the temporal evolution in congressional roll‐call behavior connected to labor policy during the New Deal and Fair Deal.